2013
DOI: 10.1093/brain/awt147
|View full text |Cite
|
Sign up to set email alerts
|

Defective cerebellar control of cortical plasticity in writer’s cramp

Abstract: A large body of evidence points to a role of basal ganglia dysfunction in the pathophysiology of dystonia, but recent studies indicate that cerebellar dysfunction may also be involved. The cerebellum influences sensorimotor adaptation by modulating sensorimotor plasticity of the primary motor cortex. Motor cortex sensorimotor plasticity is maladaptive in patients with writer's cramp. Here we examined whether putative cerebellar dysfunction in dystonia is linked to these patients' maladaptive plasticity. To tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
92
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 73 publications
11
92
2
4
Order By: Relevance
“…In the case of writer's cramp, the slower adaptation rates in Hoffland's study are in line with the findings of Hubsch et al [8] who compared the performance of 21 people with writer's cramp and 25 healthy controls in a reaching task that included a visuomotor conflict. They found that people with writer's cramp exhibited a complete loss of both inhibitory and excitatory cerebellar priming of cortical sensorimotor plasticity.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…In the case of writer's cramp, the slower adaptation rates in Hoffland's study are in line with the findings of Hubsch et al [8] who compared the performance of 21 people with writer's cramp and 25 healthy controls in a reaching task that included a visuomotor conflict. They found that people with writer's cramp exhibited a complete loss of both inhibitory and excitatory cerebellar priming of cortical sensorimotor plasticity.…”
supporting
confidence: 88%
“…They found that people with writer's cramp exhibited a complete loss of both inhibitory and excitatory cerebellar priming of cortical sensorimotor plasticity. In a visuomotor task, people with writer's cramp were also less efficient than healthy subjects at washing out a previous adaptation strategy [8]. People with focal hand dystonia also showed abnormal associative learning in an eyeblink classical conditioning paradigm [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging evidence that motor learning is deficient in people with cervical dystonia using neurophysiological measures of learning [88,89]. People with FHD are slower to adapt to visuomotor perturbations than healthy adults [90]. The only working memory task tested to date to our knowledge is the mental rotation task, a visuospatial working memory task [78].…”
Section: The Non-motor Role Of the Cerebellum In Dystoniamentioning
confidence: 99%
“…Although this role is not yet fully understood (Sadnicka et al, 2012), an elegant paper by Hubsch et al (2013) in Brain showed that in writer's cramp, a form of task-specific primary hand dystonia, the cerebellum has lost its ability to modulate sensorimotor plasticity of the motor cortex. As part of their study, they used the paired-associative stimulation protocol, a transcranial magnetic stimulation-based intervention to induce motor cortex plasticity, combined with either intermittent or continuous theta burst stimulation (TBS) over the cerebellum.…”
mentioning
confidence: 99%